2022
DOI: 10.3389/fmed.2022.897108
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Rare Heterozygous ATP8B1 Mutation in a BRIC1 Patient: Haploinsufficiency?

Abstract: Benign recurrent intrahepatic cholestasis (BRIC) is an autosomal recessive disorder characterized by recurrent cholestasis. ATPase class I, type 8B, member 1 (ATP8B1) encodes familial intrahepatic cholestasis 1 (FIC1), which acts as a phosphatidylserine reversing enzyme in the tubule membrane of hepatocytes to mediate the inward translocation of phosphatidylserine (PS). At present, dozens of ATP8B1 pathogenic mutations have been identified that mainly cause BRIC1 and progressive familial intrahepatic cholestas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The absence of this variant from major public databases, such as the Human Gene Mutation Database, Human Genetic Variation Database, and The Genome Aggregation Database, coupled with strong evidence of pathogenicity from computational predictive analyses, led to its classification as a novel pathogenic variant[ 16 , 17 ]. Novel heterozygous pathogenic ATP8B1 variants, as reported in case studies by Suzuki and Bing, shed light on the variability of BRIC1 presentation and the potential impact of haploinsufficiency on its pathogenesis[ 18 , 19 ]. These reports highlight the critical role of genetic heterogeneity in devising individualized treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of this variant from major public databases, such as the Human Gene Mutation Database, Human Genetic Variation Database, and The Genome Aggregation Database, coupled with strong evidence of pathogenicity from computational predictive analyses, led to its classification as a novel pathogenic variant[ 16 , 17 ]. Novel heterozygous pathogenic ATP8B1 variants, as reported in case studies by Suzuki and Bing, shed light on the variability of BRIC1 presentation and the potential impact of haploinsufficiency on its pathogenesis[ 18 , 19 ]. These reports highlight the critical role of genetic heterogeneity in devising individualized treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…BRIC has been considered an autosomal recessive disorder. However, several studies have demonstrated that heterozygous variants in ATP8B1 or ABCB11 genes can cause BRIC, raising the possibility of haploinsufficiency [17][18][19][20].…”
Section: Genetic Aspects Of Bric and Pficmentioning
confidence: 99%
“…BRIC1 is associated with heterozygous mutations in ATP8B1 , such as p. T888K ( Bing et al, 2022 ), c.1429 + 2T>G ( Mihara et al, 2022 ), c.1817T>C, and p. I606T ( Chen et al, 2021 ). These mutations are thought to affect the tubular membrane localization of ATP8B1, leading to impaired bile acid transport and cholestasis.…”
Section: Othersmentioning
confidence: 99%
“…A heterozygous mutation of ATP8B1 can result in the abnormal localization of the tubule membrane (Chen et al, 2021;Bing et al, 2022;Mihara et al, 2022) Benign recurrent cholestasis is characterized by the gradual development of elevated serum levels of bile acids and bilirubin over several weeks to months (Bing et al, 2022) 4-PB (van der Velden et al, 2010)…”
Section: Atp8b1mentioning
confidence: 99%